Lipodystrophy diagnosis in people living with HIV/AIDS: prediction and validation of sex-specific anthropometric models - dos Santos, André P.; Navarro, Anderson M.; Schwingel, Andiara; Alves, Thiago C.; Abdalla, Pedro P.; Venturini, Ana Claudia R.; de Santana, Rodrigo C.; Machado, Dalmo R. L. (BMC public health, 2018)
Background Body composition alterations, or lipodystrophy, can lead to serious health problems in people living with HIV/AIDS (PLWHA). The objectives of this study are to predict and validate sex-specific anthropometric predictive models for the diagnosis of lipodystrophy in PLWHA. Methods A cross-sectional design was employed to recruit 106 PLWHA (me n = 65 and women = 41) in Brazil during 2013–2014. They were evaluated using dual-energy X-ray absorptiometry, and 19 regions of body perimeters and 6 skinfold thicknesses were taken. Sex-specific predictive models for lipodystrophy diagnosis were developed through stepwise linear regression analysis. Cross-validations using predicted residual error sum of squares was performed to validate each predictive model. Results Results support the use of anthropometry for the diagnosis of lipodystrophy in men and women living with HIV/AIDS. A high power of determination with a small degree of error was observed for lipodystrophy diagnosis for men in model six (r 2 = 0.77, SEE = 0.14, r 2 PRESS = 0.73, SEE PRESS = 0.15), that included ratio of skinfold thickness of subscapular to medial calf, skinfold thickness of thigh, body circumference of waist, formal education years , time of diagnosis to HIV months , and type of combined antiretroviral therapy (cART) (with protease inhibitor “WI/PI = 1” or without protease inhibitor “WO/PI = 0”); and model five for women (r 2 = 0.78, SEE = 0.11, r 2 PRESS = 0.71, SEE PRESS = 0.12), that included skinfold thickness of thigh, skinfold thickness of subscapular, time of exposure to cART months , body circumference of chest, and race (Asian) (“Yes” for Asian race = 1; “No” = 0). Conclusions The proposed anthropometric models advance the field of public health by facilitating early diagnosis and better management of lipodystrophy, a serious adverse health effect experienced by PLWHA.